A Study on The Difference Between the Methods of Dealing of Parents with Misbehaved Students and Non-Misbehaved Ones, and its Influence on Developing Students' Competence. - Tayoub, Mahmoud; Abdullah, Etedal; Shmelleis, Afifah (Latakia University Journal - Economic and Legal Sciences Series, 2019)
هدفت الدراسة إلى التعرف على الفروق بين طرق التعامل الوالدي للتلاميذ المشكلين سلوكياً؛ وغير المشكلين وأثرها على تنمية مهارات التلاميذ معرفياً واجتماعياً في محافظة اللاذقية، تكونت عينة الدراسة من 1763 أسرة ينتسب أبنائها لمرحلة التعليم الأساسي، وقد استخدمنا الاستبيان أداة لجمع المعلومات، ثم درست إحصائيا، وأوضحت نتائج الدراسة وجود فروق معنوية ذات دلالة إحصائية بين طرق التعامل الوالدي للتلاميذ المشكلين سلوكياً وغير المشكلين، وقد اتسمت هذه الطرق بعدم الاتزان؛ والقسوة المعنوية والجسدية، وقد أظهرت الدراسة أن الأهمية النسبية لإجابات ذوي التلاميذ المشكلين سلوكياً؛ التي تدل على التعامل الوالدي العنيف مع الأبناء وصلت إلى 71.28% مقابل 65.64% لإجابات ذوي التلاميذ غير المشكلين، وأوضحت أيضاً أن آباء التلاميذ المشكلين أكثر إهمالاً لأبنائهم من آباء التلاميذ غير المشكلين سلوكياً، وأقل تعاطفاً، حيث وصلت الأهمية النسبية لإجابات ذوي التلاميذ غير المشكلين سلوكياً 73.35 % مقابل 45.75 % لإجابات ذوي التلاميذ المشكلين عن العبارة التي تدل على منح الأبناء المحبة والتعاطف الوالدي، مما يؤثر على تنمية التلاميذ معرفياً ونفسياً وصحياً. The study aimed to know the difference between the methods of dealing of parents with misbehaved students and non-misbehaved ones, and its influence on developing students socially and educationally in Latakia. The sample of survey consisted of 1763 families whose children belong to basic education gathering level, and our use of resolution tool was for information gathering. Then the results were studied statically. The result of study showed the existence of spiritual difference of static indication between the parents dealing of misbehaved students. These methods were unbalanced and spiritually and physically cruel. And the study showed that the percentage of replies is 71.28% for those who are misbehaved in comparison to 65.64% of the percentage of replies of the students which refer to dealing of parents which depends on the physical cruelty with their children. It also showed that parents of misbehaved students are more careless than those parents who have non misbehaved children. Here, the percentage of replies was 73.35% for those who are misbehaved in comparison to 45.75% for students of statements that refer to offering them love and sympathy by their parents, thus affecting the development educationally, psychologically and healthily.